Genome-wide identification and expression analysis of the MADS-box gene family during female and male flower development in Juglans mandshurica - Li, Hanxi; Li, Yuxi; Zhang, Xinxin; Cai, Kewei; Li, Yan; Wang, Qingcheng; Qu, Guanzheng; Han, Rui; Zhao, Xiyang (Frontiers in Plant Science, 2022)
The MADS-box gene family plays a crucial role in multiple developmental processes of plants, especially in floral organ specification and the regulation of fruit development and ripening. Juglans mandshurica is a precious fruit material whose quality and yield are determined by floral organ development. The molecular mechanism of J. mandshurica female and male flower development depending on MADS-box genes remains unclear. In our study, 67 JmMADS genes were identified and unevenly distributed on 15 of 16 J. mandshurica chromosomes. These genes were divided into two types (type I (Mα, Mγ, Mδ) and type II (MIKC)). The gene structure and motif analyses showed that most genes belonging to the same type had similar gene structures and conserved motifs. The analysis of syntenic relationships showed that MADS-box genes in J. mandshurica, J. sigillata, and J. regia exhibited the highest homology and great collinearity. Analysis of cis-acting elements showed that JmMADS gene promoter regions contained light, stress and hormone response cis-acting elements. The gene expression patterns demonstrated that 30 and 26 JmMADS genes were specifically expressed in the female and male flowers, respectively. In addition, 12 selected genes common to J. mandshurica female and male flowers were significantly upregulated at the mature stage and were used to validate the reliability of the transcriptome data with quantitative real-time PCR. This comprehensive and systematic analysis of J. mandshurica MADS-box genes lays a foundation for future studies on MADS-box gene family functions.